(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, the concepts of ω-open and ω-closed functions between topological spaces will be introduced and characterized. Moreover, related concepts such as ω-connectedness and ω-continuity from an arbitarary topological space into the product space will also be characterized.